Unintended Consequences of EU External Action - Burlyuk, Olga; Noutcheva, Gergana (Taylor & Francis, 2019)
This book offers a conceptualisation of unintended consequences and addresses a set of common research questions, highlighting the nature (what), the causes (why), and the modes of management (how) of unintended consequences of the European Union's (EU) external action. The chapters in the book engage with conceptual and empirical dimensions of the topic, as well as scholarly and policy implications thereof. They do so by looking at EU external action across various policy domains (including trade, migration, development, state-building, democracy promotion, and rule of law reform) and geographic areas (including the USA, Russia, the Western Balkans, the southern and eastern European neighbourhood, and Africa). The book contributes to the study of the EU as an international actor by broadening the notion of its impact abroad to include the unintended consequences of its (in)actions and by shedding new light on the conceptual paradigms that explain EU external action. This book fills the gap in IR and EU scholarship concerning unintended consequences in an international context and will be of interest to anyone studying this important phenomenon. It was originally published as a special issue of The International Spectator (Italian Journal of International Affairs). Chapters 1, 3, 7, 8 and 9 are available Open Access at https://www.routledge.com/products/9780367346492.